Correlation between Antioxidant Intake with Pro-Oxidants (MDA) and Endogenous Antioxidants (SOD) in Football Athletes (Universitas Pendidikan Indonesia, 2024)
Soccer is one of the high intensity activities requiring an intensive training since the regulatory process may increase the oxidative stress in the form of Reactive Oxygen Species (ROS). Free radicals occurring due to the imbalance of endogenous antioxidants can be measured by examining the malondialdehyde (MDA) and Superoxide Dismutase (SOD) levels as endogenous antioxidants. This outcome will affect the formation of Hemoglobin (Hb), automatically affecting the athlete ability to bind oxygen and their VO2Max. The average SOD level of soccer athletes at the Student Sports Education and Training Center (PPLP) was 45.945 U/mg. This study is a descriptive study with a cross-sectional design aimed to determine the correlation between antioxidant intake with pro-oxidants (MDA) and endogenous antioxidants (SOD) at the same research period. In this study, the total sampling technique was chosen. A total of 33 soccer athletes of PPLP Medan, from both the main and reserve teams, participated in this study. Data were analyzed using univariate, bivariate, and multivariate analysis by employing linear regression statistical tests. The results showed that there was a correlation between antioxidant intake with MDA and SOD levels of soccer athletes with p0.005. The results of multivariate analysis showed that the most influential variable on MDA levels was vitamin C intake, affecting the decrease in MDA levels by 5.545 times. Meanwhile, for SOD levels, the most influential variable was zinc intake, affecting the increase by 6.354 times. In conclusion, there is a correlation between antioxidant intake with MDA and SOD levels, where MDA levels are strongly influenced by vitamin C intake while SOD levels are influenced by zinc intake.